Fall and Revilitazion Traditional Game in Indonesia at 1990-2010 - Hendi Irawan; Januar Barkah; Muhammad Abdul Karim (Tsaqofah, 2018)
The number of traditional game in Indonesia decreasing since change with new style of society and religion, but in late 20th century, with more popular of video game in Indonesia made big change in society and the number of traditional game more decreasing than before.Documentation of traditional game has started either by goverment before modern entertainment more popular in Indonesia at 1980-2000’s, but revilitazion not much do in grassroot. The communities and goverment started to preserving theintangible heritage with many ways also from, either in local or national above 2000's when they reliaze many traditional game has disappear and Indonesian heritage under threat.